A Case Study of Mapping the Heating Storage Capacity in a Multifamily Building within a District Heating Network in Mid-Sweden - Abolfazl Hayati; Jan Akander; Martin Eriksson (Buildings, 2022)
The building sector accounts for a third of the total energy use in Sweden, and district heating provides half of the heating needs. The peak demand loads within a district heating network occur both regularly and irregularly and impose a burden on the energy company to fulfill the demand, often by using more expensive and less environmentally friendly resources (e.g., fossil fuels) instead of the waste heat from industry or biofuels. Heat storage during hours of less demand and prior to colder periods can be used for load management and sustainable planning of energy supply, as well as reduction of total greenhouse gas emissions. Thus, heat supply to the building can be lowered temporarily during the peak power period to utilize the stored thermal energy within the building thermal inertia. The use of indoor temperature decay and the delivery of heating power to a multifamily building are studied here, and heating storage capacity and thermal inertia are calculated. During the performed decay test, the energy supply was estimated to be reduced by 61% for 5 h, which resulted in only a 0.3 °C temperature decay. Therefore, the suggested method can shave eventual peaks in supplied heat with minimal influence on the thermal comfort.